Formulasi Tepung Biofungisida Berbahan Aktif Ganda Pseudomonas Fluorescens PG 01 dan Bacillus Polymixa BG 25 - . Widodo; Suryo Wiyono (Institut Pertanian Bogor, 2012)
The objective of this study is to determine effective carrier materials and additives which is able to keep the bioperformance, including antibiosis activity to Phytophthora capsici and Colletotrichum acutatum and plant growth promoting effect, of two antagonistic bacteria Psedomonas fluorescens PG 01 and Bacillus polymixa BG 25 in biofungicide powder formulations. Talc and bentonite formulations were effective after 3 months of storage, while tapioca were only effective to B. polymixa up to 3 months of storage. Additive materials that can enhance the antibiosis activity of the bacteria, keeping up the growth and no toxicity effect to chili seedlings were crab shell powder 0.25% and MnSO4 1 to 2%. After eight months storage with 20% moisture content, the bacteria population survived in powder formulation developed in this study was still suitable for seed treatment and/or after transplanting through soil drenching with water. In this period of storage, population of the two bacteria was 106 cfu/g formulation.